Solid state solar cell made from nanocrystalline TiO2 with a fluorene-thiophene copolymer as a hole-conductor - Ravirajan, P.; Haque, S.A.; Poplavskyy, D.; Durrant, J.R.; Bradley, D.D.C.; Nelson, J. (My University, 2003)
We study the charge recombination kinetics and photovoltaic performance of composites of poly (9,9-dioctylfluorene-co-bithiophene) polymer with nanocrystalline TiO2. Transient optical spectroscopy confirms that photoexciation of the polymer leads to electron transfer to the TiO2 and indicates that charge recombination is slow with a half-life of 100μs to 10ms. Polymer penetration into thick porous TiO2 layers is improved by melt-processing and treatment of the TiO2 surface. We study the photovoltaic characteristics of devices with different layer thickness and interface morphology. Quantum efficiency (QE) of all devices is increased by reducing the TiO2 and polymer layer thickness. Inserting a thin porous TiO2 layer in to a thin bi-layer device increases the QE by a factor of five. The improved device shows peak QE and monochromatic power conversion efficiencies of over 11% and 1% at 440nm respectively. The device produced a short-circuit current density of 300μAcm-2, a fill factor of 0.24 and an open-circuit voltage of 0.8V under AM1.5 illumination. The fill factor is increased from 0.24 to 0.40 by introducing an additional dip-coating layer and overall power conversion efficiency is increased by 50%. However, the device produced degraded current-voltage characteristics. We investigate this using an alternative polymers and different top contact metals.
Keywords: Nanocrystalline TiO2; Polymer; Solar cells